2015
DOI: 10.1016/j.nuclphysb.2015.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Planar ordering in the plaquette-only gonihedric Ising model

Abstract: In this paper we conduct a careful multicanonical simulation of the isotropic $3d$ plaquette ("gonihedric") Ising model and confirm that a planar, fuki-nuke type order characterises the low-temperature phase of the model. From consideration of the anisotropic limit of the model we define a class of order parameters which can distinguish the low- and high-temperature phases in both the anisotropic and isotropic cases. We also verify the recently voiced suspicion that the order parameter like behaviour of the st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…where to maintain a one-to-one correspondence between the σ and τ spin configurations on a periodic lattice the L 2 constraints of the τ -spins, L z=1 τ x,y,z = 1, must be satisfied and respected by an additional factor of 2 L×L in the partition function [10]. The resulting Hamiltonian when J x = J y = 1 is then…”
Section: Model and Observablesmentioning
confidence: 99%
“…where to maintain a one-to-one correspondence between the σ and τ spin configurations on a periodic lattice the L 2 constraints of the τ -spins, L z=1 τ x,y,z = 1, must be satisfied and respected by an additional factor of 2 L×L in the partition function [10]. The resulting Hamiltonian when J x = J y = 1 is then…”
Section: Model and Observablesmentioning
confidence: 99%
“…Since in references [36][37][38][39]41,42] we employed multicanonical simulations giving a flat energy distribution, reweighting techniques [64][65][66][67] can be used to get an estimator of the energy probability densities at different temperatures. β eqw is chosen systematically to minimise…”
Section: Simulational Considerationsmentioning
confidence: 99%
“…The κ = 0 plaquette Hamiltonian, on the other hand, has a strong first-order phase transition [35] and recent high-precision multicanonical simulations [36][37][38][39] have revealed that it displays non-standard finite-size scaling properties at this transition. In the sequel we will describe how this non-standard scaling is a consequence of a macroscopic low-temperature phase degeneracy in the 3d plaquette Ising model and also discuss the implications of this degeneracy for the nature of the low-temperature phase and the definition of an order parameter [40][41][42]. Recent work on quantum spin versions of the plaquette model has also shown that the symmetries of the plaquette Hamiltonian and the low-temperature degeneracy are instrumental in the appearance of a novel form of topological defect, a fracton [43][44][45][46][47][48], and we sketch their appearance via a partial gauging construction using the quantum dual of the plaquette model.…”
Section: Introductionmentioning
confidence: 99%
“…The other interesting property of the system is that the relaxation to the equilibrium state is very slow, like in spin glasses [20,39,41,42,43,44,45,46,51,54,52,55,56,57,58]. The reason is rooted in high symmetry of the system (3.9), its energy states are exponentially degenerated [17,18,19].…”
Section: Monte-carlo Simulation Of Gonihedric Systems In Various Dimementioning
confidence: 99%